ETHNO-DEMOGRAPHIC INDICATORS OF NATIONAL-MIXED FAMILIES OF THE POPULATION OF CENTRAL KAZAKHSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The Central region of Kazakhstan, characterized by a multi-ethnic composition of the population, is an ethno-contact zone of interaction of different cultures and traditions. National-mixed marriages and families in Central Kazakhstan are one of the most important factors contributing to the integration and mutual understanding of different ethnic groups and communities. This socialinstitution, which is a micro- cell of Kazakhstani society, has undergone a number of changes over the past few decades due to the collapse of the former Soviet Union and the independent development of our multi-ethnic republic. This report considers the factors that have a direct or indirect impact on the formation of marriage relations between different ethnic groups in the region, at the same time contributing to the preservation of integration and tolerance of Kazakh society. On the basis of statistical materials of national censuses of the population of the Republic of Kazakhstan, conducted every decade, the peculiarities of the ethnic composition of the region, the size of both single-ethnic and ethnic-mixed families were revealed.
Keywords: ethnic-mixed families, demography, population censuses, ethnic composition, family and marriage, household